2008
DOI: 10.1097/cej.0b013e328305a10b
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage and antioxidant status in patients with cervical intraepithelial neoplasia and carcinoma of the cervix

Abstract: Free radicals that induced lipid peroxidation and DNA damage have been implicated in many diseases including cancer. Cellular antioxidant defense plays an important role in neoplastic disease to counteract oxidative damage. This study aims to investigate the status of oxidative damage by measuring plasma malondialdehyde (MDA) level and urinary 8-hydroxydeoxyguanosine (8-OHdG), and the level of antioxidant enzymes superoxide dismutase, glutathione peroxidase, and catalase in patients with cervical intraepitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
2
23
2
5
Order By: Relevance
“…43 Oxidative damage is markedly increased in CIN. 44 It is possible that TG2 shuttles in the nucleus to protect the cells by modulating hypoxia-mediated transcriptional events, possibly by attenuating HIF activation of pro-cell death genes as observed during ischemic stroke. 45 The purpose of our study has been to clarify the role of TG2 during the evolution of CIN lesions.…”
Section: Transglutaminase2 In Hpv Lesionsmentioning
confidence: 99%
“…43 Oxidative damage is markedly increased in CIN. 44 It is possible that TG2 shuttles in the nucleus to protect the cells by modulating hypoxia-mediated transcriptional events, possibly by attenuating HIF activation of pro-cell death genes as observed during ischemic stroke. 45 The purpose of our study has been to clarify the role of TG2 during the evolution of CIN lesions.…”
Section: Transglutaminase2 In Hpv Lesionsmentioning
confidence: 99%
“…A number of authors [19][20][21] have shown that excessive formation of free radicals and inactivation of antioxidant enzyme on the background of antitumor laser therapy ensures the accumulation of toxic products of oxidative stress intensifying the severity of endogenous tumor intoxication. Secondary metabolic disorders are accompanied by toxic damage of cell membranes of various internal organs and tissues, which is often the limiting factor for further treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative status has been reported altered in blood of patients with cervical intraepithelial neoplasia (CIN). Studies on serum of patients with CIN and carcinoma of the cervix showed alterations in lipid peroxidation and impairment of antioxidant systems, either enzymatic or not [24,25]. Additionally, other blood indicators of oxidative stress such as TBARS, ALA-D reactivation index, and vitamin C content were reported altered (increased or decreased) in both low-grade and high-grade SIL, as well as cervical cancer [26].…”
Section: Discussionmentioning
confidence: 99%